Intra-tumoral production of IL18, but not IL12, by TCR-engineered T cells is non-toxic and counteracts immune evasion of solid tumors. (2nd January 2018) - Kunert, A.; Chmielewski, M.; Wijers, R.; Berrevoets, C.; Abken, H.; Debets, R.
ABSTRACT: Adoptive therapy with engineered T cells shows promising results in treating patients with malignant disease, but is challenged by incomplete responses and tumor recurrences. Here, we aimed to direct the tumor microenvironment in favor of a successful immune response by local secretion of interleukin (IL-) 12 and IL-18 by sadministered T cells. To this end, we engineered T cells with a melanoma-specific T cell receptor (TCR) and murine IL-12 and/or IL-18 under the control of a nuclear-factor of activated T-cell (NFAT)-sensitive promoter. These T cells produced IL-12 or IL-18, and consequently enhanced levels of IFNγ, following exposure to antigen-positive but not negative tumor cells. Adoptive transfer of T cells with a TCR and inducible (i)IL-12 to melanoma-bearing mice resulted in severe, edema-like toxicity that was accompanied by enhanced levels of IFNγ and TNFα in blood, and reduced numbers of peripheral TCR transgene-positive T cells. In contrast, transfer of T cells expressing a TCR and iIL-18 was without side effects, enhanced the presence of therapeutic CD8 + T cells within tumors, reduced tumor burden and prolonged survival. Notably, treatment with TCR+iIL-12 but not iIL-18 T cells resulted in enhanced intra-tumoral accumulation of macrophages, which was accompanied by a decreased frequency of therapeutic T cells, in particular of the CD8 subset. In addition, when administered to mice, iIL-18 but not iIL-12 demonstrated a favorable profile of T cell co-stimulatory and inhibitory receptors. In conclusion, we observed that treatment with T cells engineered with a TCR and iIL18 T cells is safe and able to skew the tumor microenvironment in favor of an improved anti-tumor T cell response.